Analysis of Red Algae Seaweed (Eucheuma cottonii) Cultivation in Jerowaru District, Lombok Regency - Sri Wahyuni; Muhammad Nursan; Asri Hidayati (Jurnal Biologi Tropis, 2023)
Red algae seaweed (Eucheuma cottonii) is a very important commodity to be developed because it has a high selling price and production. The purpose of this study is to determine the cultivation of red algae seaweed (Eucheuma cottonii) in Jerowaru District, East Lombok Regency, analyze the feasibility of red algae seaweed cultivation business (Eucheuma cottonii) in Jerowaru District, East Lombok Regency, find out the obstacles faced in conducting red algae seaweed (Eucheuma cottonii) cultivation business in Jerowaru District, East Lombok Regency. The method used is the descriptive method. Data collection was carried out by survey techniques. Determination of the research area is carried out by purposive sampling or deliberately. The determination of the number of respondents was carried out by the Slovin method, which was 42 respondents. The collection of respondents was carried out using the Proportional Random Sampling method. The results showed that (1) the average profit obtained is IDR 19,532,149.98 per arable land area or IDR 23,902,980.75 per hectare during one harvest season; (2) the cultivation of red algae seaweed (Eucheuma cottonii) in Jerowaru District is feasible; (3) obstacles faced by farmers in red algae seaweed cultivation business (Eucheuma cottonii) in Jerowaru District, namely lack of capital, lack of labor, pest attacks, diseases, weeds, and erratic weather. It is recommended for farmers to cultivate red algae seaweed (Eucheuma cottonii) in Jerowaru District to increase productivity and be able to overcome the obstacles faced by participating in seaweed cultivation training activities held by related agencies.